Antioxidant Mechanism of Rutin on Hypoxia-Induced Pulmonary Arterial Cell Proliferation - Qian Li; Yanli Qiu; Min Mao; Jinying Lv; Lixin Zhang; Shuzhen Li; Xia Li; Xiaodong Zheng (Molecules, 2014)
Reactive oxygen species (ROS) are involved in the pathologic process of pulmonary arterial hypertension as either mediators or inducers. Rutin is a type of flavonoid which exhibits significant scavenging properties on oxygen radicals both in vitro and in vivo. In this study, we proposed that rutin attenuated hypoxia-induced pulmonary artery smooth muscle cell (PASMC) proliferation by scavenging ROS. Immunofluorescence data showed that rutin decreased the production of ROS, which was mainly generated through mitochondria and NADPH oxidase 4 (Nox4) in pulmonary artery endothelial cells (PAECs). Western blot results provided further evidence on rutin increasing expression of Nox4 and hypoxia-inducible factor-1α (HIF-1α). Moreover, cell cycle analysis by flow cytometry indicated that proliferation of PASMCs triggered by hypoxia was also repressed by rutin. However, N-acetyl-L-cysteine (NAC), a scavenger of ROS, abolished or diminished the capability of rutin in repressing hypoxia-induced cell proliferation. These data suggest that rutin shows a potential benefit against the development of hypoxic pulmonary arterial hypertension by inhibiting ROS, subsequently preventing hypoxia-induced PASMC proliferation.